De novo Ring Chromosome 6 in a Child with Multiple Congenital Anomalies - Ahmad, Ahzad Hadi; Ramli, Siti Fatimah; Tan, May Loong; Salahshourifar, Iman; Alwi, Zilfalil; Mohd Yusoff, Narazah (Kobe University School of Medicine, 2010)
Ring chromosome 6, especially if it is de novo, is a rare occurrence. The phenotype of patients with ring chromosome 6 can be highly variable ranging from almost normal to severe malformations and mental retardation. The size and structure of the ring chromosome as well as the level of mosaicism are important factors in determining the clinical phenotype. Here we report an eight month-old child, a product of a non consanguineous marriage, who presented with developmental retardation, hypertelorism, microcephaly, flat occiput, broad nasal bridge, large ears, micrognathia, wide spaced nipples, protruding umbilicus, short stubby fingers, clinodactyly, single palmar crease, short neck with no obvious webbing, and congenital heart defect. Conventional karyotyping and Whole Chromosome Paint of the peripheral leukocytes showed 46,XY,r(6)(p25q27) karyotype with plausible breakpoints at p25 and q27 end. Conventional karyotyping of both parents showed normal karyotype. To the best of our knowledge, this is the first report of a Malay individual with ring chromosome 6, and this report adds to the collective knowledge of this rare chromosome abnormality.